Investigation of Chips in Ultrasonic High Speed Micro Milling of Ti6Al4V Alloy - Mahmat, Aybars; Tosun, Nihat; Ağar, Salih (Osman SAĞDIÇ, 2023)
The machinability of Ti6Al4V alloy, the processing parameters with ultrasonic and conventional micro milling, and the effects of different cooling/lubrication methods on the chip thickness ratio and chip form were investigated experimentally in this study. While this research was being carried out, in experimental studies, dry machining under 0.02 mm constant depth of cut, 0.66 mm/s constant feed and 20,000, 40,000 and 60,000 rpm speed processing conditions, nano Al2O3 particle added borax-ethylene glycol mixture and olive oil-borax-ethylene glycol mixture The minimal amount of lubrication (MMY) method with nano-cutting fluid containing 50-100 micrometer size Al2O3 used carbide and TiSiN coated carbide cutting tools. In ultrasonic micro milling, two different vibration frequencies (20 and 30 kHz) of constant amplitude were applied to the cutting tool. Discontinuous chip form was obtained in all experimental studies. It was determined that the cooling method and the cutting tool had no effect on the chip form.

Ti6Al4V alaşımının işlenebilirliği, ultrasonik ve geleneksel mikro frezeleme ile işlem parametreleri ve farklı soğutma/yağlama yöntemlerinin talaş kalınlık oranı ve talaş formuna etkileri bu çalışmada deneysel olarak araştırıldı. Bu araştırma yapılırken deneysel çalışmalarda 0.02 mm sabit talaş derinliği, 0.66 mm/s sabit ilerleme ve 20.000, 40.000 ve 60.000 dev/dak devir sayısı işleme şartlarında kuru işleme, nano Al2O3 partikül katkılı boraks-etilen glikol karışımı ve zeytinyağı- boraks-etilen glikol karışımı 50-100 mikro metre boyutlu Al2O3 içeren nano kesme sıvılı minimum miktarda yağlama (MMY) yöntemi, karbür ve TiSiN kaplamalı karbür kesici takımlar kullandı. Ultrasonik mikro frezelemede, sabit genlikte iki farklı titreşim frekansı (20 ve 30 kHz) kesici takıma uygulandı. Deneysel çalışmaların tümünde süreksiz talaş formu elde edildi. Talaş formuna soğutma yönteminin ve kesici takımının bir etkisi olmadığı belirlendi.
Ti6Al4V Alaşımının Ultrasonik Yüksek Hızlı Mikro Frezelenmesinde Talaşların İncelenmesi
Keywords: Engineering; Mühendislik